Policy Analysis and Organizational Effectiveness - Kasmita, Maya; Firman, M. Jihad (Universitas Negeri Makassar, 2023)
The application of Makassar Mayor Regulation Number 98 of 2016 concerning Position, Organizational Structure, Duties and Functions and Work Procedures of the Makassar City Cooperatives, Small and Medium Enterprises Service is in the context of increasing the effectiveness of the work of the Makassar City Office of Cooperatives and UMKM. In this study trying to see the impact of organizational policies on organizational effectiveness by using the six variable elements of management policies and practices. The six elements are strategic goal setting, resource search and utilization, achievement environment, communication process, leadership and decision making, and organizational adaptation and innovation. This qualitative research uses a case study approach. The data analysis technique is the Miles and Huberman model , which consists of data reduction, data display/presentation, and conclusion/verification. The results of the study indicate that organizational effectiveness at the Makassar City Cooperative and MSME Office has not gone well, this can be seen from a number of things, including the absence of specialized personnel managing education and training and special staff (Bachelors) in the field of cooperatives and working environment conditions (achievement environment). in the Office of Cooperatives and SMEs that have not been effective. Improper placement of employees by not paying attention to the educational background and specialization / expertise of employees so that it takes time in the adjustment process and reduces the number of education and training programs due to limited allocation of funds .